Space and Time in the Religious Life of the Near East. - Wyatt, Nicolas (Biblical seminar., 2001)
Space and time are basic features of the world-view, even the theology, of many religions, ancient and modern. How did the world begin, and how will it end? What is the importance of religious architecture in symbolizing sacred space? Where and how do we locate the self? The divine world? Wyatt''s textbook treats ancient Near Eastern religions from a perspective that allows us to access how religion shapes and orders the world of human thought and experience. The book is designed especially for classroom use, each chapter provided with suggested reading, copious quotations from ancient texts a.